Universal e particular law in the light of the canonical hermeneutic of St. John Paul II - GEROSA, LIBERO (Prawo Kanoniczne, 2017)
While the mystical expression “to see beyond” allows John Paul II to “trace the direction” for the development of a new canonical hermeneutic, apt for assuming the great missionary challenges of the of the third millennium, the normative novelty introduced by him and the methodological direction dealt by him allow his conviction, that the Church is “a house and school of communion”, to become the programmatic force of all the structural reforms initiated by him. This reform of the Church, which is “communio Ecclesiarum”, in its communion and missionary aspects, finds its central core at the level of the relationships between the universal law and the particular law. Or rather, it is precisely the so called “corpus iuris commune” that, thanks to John Paul II’s methodological and hermeneutic direction, can redefine the specific and interactive functions existing between universal canon law and particular canon law: the first must guarantee the unity, without reducing it to uniformity: the second instead should guarantee the plurality, without falling into particularism